High-toughness low-melting-point nylon resin as well as preparation method and application thereof
By using long-carbon chain dibasic acid, long-carbon chain dibasic acid and ether-containing amino acids for polycondensation reaction, high-toughness, low melting point, and low water absorption, high-toughness and low melting point nylon resins are prepared, which solves the problem of poor performance of nylon resins in the prior art, and realizes the preparation of diversified products and industrial continuous production.
Patent Information
- Application Number
- CN202510126850.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-27
AI Technical Summary
It is difficult to prepare a high-toughness, low melting point, low water absorption, diversified products, and easy to process. It has a complex production process and is suitable for industrial continuous production.
Long carbon chain dibasic acid, long carbon chain dibasic acid and ether-containing amino acids are used as the main components, and water is used as the reaction medium to reduce the melting point of the nylon resin and improve its toughness through polycondensation reaction.
Nylon resins that achieve high toughness, low melting point, low water absorption and diversified products have a relative viscosity of up to 2.52, a tensile strength of up to 47MPa, an elongation of breaking as high as 382%, a bending strength of up to 68MPa, a notch impact strength of up to 32kJ/m2, a melting point as low as 122℃, and a water absorption rate of up to 0.36%.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a nylon resin and a preparation method and application thereof, and in particular to a high-toughness and low-melting-point nylon resin and a preparation method and application thereof. Background Art
[0002] Polyamide (PA), commonly known as nylon, is obtained by polycondensation of dibasic acid and diamine or amino acid. It is a general term for resins containing repeated amide groups on the molecular chain. Nylon is the base resin with the largest output, the most varieties, the widest application and excellent comprehensive performance among the five major general engineering plastics. The reason why nylon ranks first among the five major engineering plastics is mainly because it has many excellent properties and has outstanding advantages in mechanical properties, chemical properties, thermal properties, etc. After more than 70 years of development, the application of nylon has gradually expanded from spinning fibers to films, engineering plastics and other fields.
[0003] Low-melting-point nylon refers to a modified product with a lower melting point than conventional nylon. Because its molecular chain contains polar amide groups, it has good bonding properties to many polar materials, and has the advantages of narrow melting range, high softening point, fast curing, resistance to organic solvent dry cleaning, and no pollution to the environment during use. Therefore, it has been widely used in hot melt adhesives, non-woven fabrics, engineering plastics and other fields. At present, the methods for synthesizing low-melting-point nylon include random copolymerization, blending and some other modification methods. Among them, random copolymerization modification is the most commonly used method for preparing low-melting-point nylon. Its main characteristics are relatively simple process and excellent effect. It can be widely used in hot melt adhesives, fiber spinning and other fields. However, there are problems such as poor heat resistance of the copolymer monomer, resulting in yellowing of the polymer, high monomer residue and inability to take into account mechanical properties.
[0004] CN102492135A discloses a method for synthesizing dimer acid type nylon hot melt adhesive, which uses dimer acid, aliphatic dicarboxylic acid and aliphatic diamine as raw materials, and adds a catalyst, an alcohol aqueous solution and an auxiliary agent to prepare a low melting point nylon. However, due to the use of dimer acid in the formula, the color of the final product is yellowish.
[0005] CN109970969A discloses a method for preparing a ternary copolymerized low-melting-point nylon. The low-melting-point nylon is mainly copolymerized by 2,4-diaminotoluene, aliphatic diamine, aliphatic dibasic acid, and caprolactam (the molar percentages are: 10-38%, 10-38%, 35-48%, and 5-30%), and has a melting point between 70 and 150°C. Although the preparation method is simple and has strong operability, the amino group of 2,4-diaminotoluene is directly connected to the benzene ring, so the reaction activity is low, which affects the molecular weight of the low-melting-point nylon. In addition, due to the presence of caprolactam, a certain amount of monomers and oligomers are easily left in the final product, which limits its application field.
[0006] CN109722020A discloses an ultra-tough nylon composite material toughened by an amine-functionalized polyolefin elastomer and a preparation method thereof. The ultra-tough nylon composite material is composed of 50 to 97 parts of nylon resin, 2 to 50 parts of amine-functionalized polyolefin elastomer and 0 to 0.8 parts of antioxidant. Although the preparation process does not require the addition of peroxide cross-linking agent and polar monomer, side reactions such as cross-linking and degradation during processing are effectively avoided, and the prepared high-tough nylon composite material has good processing performance, tensile strength and toughness, due to the poor compatibility of the amine-functionalized polyolefin elastomer with the nylon matrix, while improving the toughness of the nylon resin, it is inevitable to sacrifice other aspects of performance, and it is impossible to achieve a significant reduction in the melting point of the nylon resin, and it is impossible to take into account all aspects of performance.
[0007] In summary, it is urgent to find a high-toughness, low-melting-point nylon resin and its application with high toughness, low melting point, low water absorption, product diversification, and easy processing, as well as a preparation method of a high-toughness, low-melting-point nylon resin with few by-products, simple production process, and suitable for industrial continuous production. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a high-toughness, low-melting-point nylon resin and its application which has high toughness, low melting point, low water absorption, diversified products and easy processing.
[0009] The technical problem to be further solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a high-toughness, low-melting-point nylon resin with less by-products, simple production process and suitable for industrial continuous production.
[0010] The technical solution adopted by the present invention to solve its technical problem is as follows: a high-toughness, low-melting-point nylon resin is mainly made of the following components: a long-chain dibasic acid, a long-chain diamine, an amino acid containing an ether bond, a catalyst and a capping agent, and water is used as a reaction medium.
[0011] The inventive concept of the present invention is that the amide bond in the nylon molecular chain has a very large influence on its thermal properties. If there is no amide bond, its chemical structure is equivalent to polyethylene, and there is no hydrogen bond between molecules. Only weak van der Waals forces interact with each other. At this time, nylon is just a polymer with a melting point of 120°C, while the melting point of nylon 6 is as high as about 220°C. It can be seen that the existence of amide bonds increases the melting point of nylon. Reducing the proportion of amide bonds and increasing the number of carbon atoms between each amide bond can reduce the melting point of nylon to a certain extent. For example, the melting point of nylon 12 is about 178°C. Based on the factors affecting the melting point of nylon, reducing the melting point of nylon should start from the interaction force, rigidity and flexibility, regularity and hydrogen bonds between nylon molecular chains. The present invention uses long carbon chain dibasic acid and long carbon chain diamine as the main matrix, and introduces a certain proportion of amino acids containing ethoxy (i.e., ether bond) repeating units as copolymerization modification components to destroy the regularity of nylon molecular chains, reduce the hydrogen bond density and crystallinity between nylon molecular chains, thereby achieving the purpose of lowering the melting point of nylon resin and improving the toughness of nylon resin; at the same time, since the matrix molecules have a long carbon chain structure, their macroscopic properties show high impact resistance and low water absorption.
[0012] Preferably, the molar ratio of the long carbon chain dibasic acid to the long carbon chain diamine is 1:1.0-1.10.
[0013] Preferably, the amounts of the ether bond-containing amino acid, catalyst, end-capping agent and water are 10.0-30.0%, 0.18-0.42% (more preferably 0.18-0.30%), 0.3-0.8% (more preferably 0.3-0.6%) and 40-50% of the total mass of the long-chain dibasic acid and the long-chain diamine, respectively.
[0014] Preferably, the general structural formula of the long carbon chain dibasic acid is HOOC-(CH2) n -COOH, wherein n is an integer of 8 to 16. More preferably, the long carbon chain dibasic acid includes one or more of sebacic acid, dodecanedioic acid or octadecanedioic acid.
[0015] Preferably, the long carbon chain diamine has the general structural formula of NH2-(CH2) n -NH2, wherein n is an integer of 10 to 18. More preferably, the long carbon chain diamine includes one or more of decanediamine, dodecanediamine or octadecanediamine.
[0016] Preferably, the amino acids containing ether bonds include 1-amino-3,6,9,12-tetraoxopentadecane-15-oic acid, 1-amino-3,6,9,12,15-pentaoxoctadecane-18-oic acid, 1-amino-3,6,9,12,15,18-hexaoxohexadecan-21-oic acid, 1-amino-3,6,9,12,15,18,21-heptaoxohexadecan-24-oic acid, -acid, 1-amino-3,6,9,12,15,18,21,24-octaoxocosatriacosane-27-acid, 1-amino-3,6,9,12,15,18,21,24,27-nonaoxatriacontane-30-acid or 1-amino-3,6,9,12,15,18,21,24,27,30-decaoxatriacontane-33-acid and the like.
[0017] Preferably, the catalyst includes one or more of sodium hypophosphite, potassium hypophosphite, calcium hypophosphite or magnesium hypophosphite, etc. The catalyst functions to catalyze the polycondensation reaction of the dibasic acid and the diamine.
[0018] Preferably, the end-capping agent includes one or more of monoamino or monocarboxyl silicone, Shin-Etsu modified silicone oil KF-864, KF-865, KF-868 or X-22-3701E, etc. The end-capping agent is a monofunctional group, and its function is to achieve end-capping, regulate the molecular weight, and obtain a nylon resin with a desired molecular weight.
[0019] The present invention can adjust the melting point of the nylon resin between 122 and 160° C. by adjusting the type and content of the copolymer components, thereby achieving customization of product performance to meet specific application sites with different performance requirements.
[0020] The technical solution adopted by the present invention to further solve the technical problem is as follows: A method for preparing a high-toughness low-melting-point nylon resin comprises the following steps: (1) Adding a long carbon chain dibasic acid, a long carbon chain diamine and water into a reaction kettle, stirring at room temperature to form a salt, and obtaining a nylon salt solution; (2) An amino acid containing an ether bond, a catalyst and a capping agent are added to the nylon salt solution obtained in step (1), the air in the reaction kettle is replaced with an inert gas and filled with the inert gas, a polycondensation reaction is carried out, the inert gas is filled again, and the material is discharged to obtain a high-toughness, low-melting-point nylon resin.
[0021] Preferably, in step (2), the specific reaction process of the polycondensation reaction is: firstly carry out a temperature-raising and pressure-maintaining reaction, slowly release the gas and carry out a second temperature-raising and pressure-maintaining reaction, then release the gas to normal pressure, discharge the water in the system, and gradually evacuate the system to carry out a pressure-reducing reaction.
[0022] Preferably, the one-time temperature-raising and pressure-maintaining reaction refers to: raising the temperature to 210-220° C., maintaining the pressure in the autoclave at 2.0-2.5 MPa, and reacting for 1.5-2.0 hours. The purpose of the one-time temperature-raising and pressure-maintaining reaction is mainly to pre-condense and form oligomers.
[0023] Preferably, the slow release and secondary temperature and pressure maintenance reaction means: continue to heat up to 240-250°C, slowly release gas during the heating process to keep the pressure in the kettle at 1.0-1.5MPa (more preferably 1.1-1.3MPa), and react for 1.0-2.0h (more preferably 1.3-1.8h). The purpose of the secondary temperature and pressure maintenance reaction is mainly to carry out chain growth reaction, discharge water in the system and water generated by polycondensation reaction, promote the reaction in the positive direction, and gradually increase the molecular weight.
[0024] Preferably, the stepwise vacuuming for decompression reaction means: first vacuuming to -0.01~-0.03MPa, maintaining pressure reaction for 15~25min, then vacuuming to -0.03~-0.05MPa, maintaining pressure reaction for 15~25min, and finally vacuuming to -0.05~-0.07MPa, maintaining pressure reaction for 12~30min. The vacuum degree of the latter vacuuming is greater than the previous one. Before gradually vacuuming, venting to normal pressure can further discharge the moisture inside the system. The purpose of gradual vacuuming is to further discharge the water generated by the post-condensation reaction, i.e., the decompression reaction process, to promote the reaction in the positive direction, and further increase the molecular weight; the vacuum degree of the early vacuuming is relatively small, in order to avoid the reaction as violent as possible, resulting in the blockage of the vacuum pipe by the extracted moisture and oligomers, and then gradually increase the vacuum degree to extract as much moisture as possible to obtain the nylon resin with the expected molecular weight.
[0025] More preferably, the stepwise vacuuming for reduced pressure reaction means: first vacuuming to -0.01 to -0.02 MPa, then maintaining the pressure for 20 to 25 min, then vacuuming to -0.03 to -0.04 MPa, then maintaining the pressure for 20 to 25 min, and finally vacuuming to -0.05 to -0.06 MPa, then maintaining the pressure for 20 to 30 min.
[0026] Preferably, before the polycondensation reaction, the air in the reactor is replaced with an inert gas for 3 to 4 times and the inert gas is filled to 0.1 to 0.2 MPa.
[0027] Preferably, after the polycondensation reaction, an inert gas is charged to 0.2-0.3 MPa.
[0028] Preferably, the inert gas includes one or more of carbon dioxide, nitrogen, argon or helium, etc. The inert gas used in the present invention is a high-purity gas with a purity of ≥99.999%.
[0029] The technical solution adopted by the present invention to further solve its technical problem is as follows: the high-toughness and low-melting-point nylon resin is used in technical fields such as automobile oil pipes, water pipes or energy storage equipment hoses.
[0030] The beneficial effects of the present invention are as follows: (1) The high-toughness, low-melting-point nylon resin of the present invention has the characteristics of high toughness, low melting point, low water absorption, product diversification, and easy processing. Among them, the relative viscosity is as high as 2.52, the tensile strength reaches 47MPa, the elongation at break is as high as 382%, the flexural strength reaches 68MPa, and the notched impact strength is as high as 32kJ / m 2 , with a melting point as low as 122°C and a water absorption rate as low as 0.36%; it can replace imported high-performance nylon resins and be used in technical fields such as automotive oil pipes, water pipes or energy storage equipment hoses; (2) The product obtained by the method of the present invention has few by-products, a simple production process, and is suitable for industrial continuous production. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the embodiments.
[0032] The inert gas used in the examples of the present invention and the comparative examples is a high-purity gas with a purity of ≥99.999%; the raw materials or chemical reagents used in the examples of the present invention, unless otherwise specified, are obtained through conventional commercial channels.
[0033] A high-toughness low-melting-point nylon resin embodiment 1 to 8 A high-toughness, low-melting-point nylon resin embodiment 1 to 8 is made of the following components: a long carbon chain dibasic acid, a long carbon chain diamine, an amino acid containing an ether bond, a catalyst and a capping agent, and water is used as a reaction medium; the components and amounts are shown in Table 1.
[0034] The components and dosages of Comparative Examples 1 and 2 are shown in Table 1.
[0035] Table 1 Components and dosages of high-toughness low-melting-point nylon resin Examples 1 to 8 and Comparative Examples 1 and 2 of the present invention
[0036] Note: “ / ” in the table means not added.
[0037] A method for preparing a high-toughness low-melting-point nylon resin Example 1 (1) Add 2.022 kg (10.00 mol) of long carbon chain dibasic acid sebacic acid, 1.730 kg (10.04 mol) of long carbon chain diamine decanediamine and 1.501 kg of water (water / (dibasic acid+diamine)=40%, the same below) into a reaction kettle, stir at room temperature to form salt, and obtain nylon 1010 salt solution; (2) 375.2 g of ether-bonded amino acid 1-amino-3,6,9,12-tetraoxopentadecane-15-acid, 7.5 g of catalyst sodium hypophosphite and 15.0 g of end-capping agent Shin-Etsu modified silicone oil KF-864 were added to the nylon 1010 salt solution obtained in step (1), and the air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.2 MPa, and then a polycondensation reaction was carried out: first, the temperature was raised to 212°C, and the pressure in the reactor was maintained at 2.0 MPa, and a temperature-raising and pressure-maintaining reaction was carried out for 1.5 h, and then the temperature was continued to be raised to 250°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor at 1.2 MPa, and a second temperature-raising and pressure-maintaining reaction was carried out for 1.3 h. h later, the pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first, evacuate the system to -0.02 MPa, and then maintain the pressure for 20 min. Then, evacuate the system to -0.04 MPa, and then maintain the pressure for 20 min. Finally, evacuate the system to -0.06 MPa, and then maintain the pressure for 30 min. High-purity nitrogen was then introduced to 0.2 MPa, and the material was discharged to obtain a high-toughness, low-melting-point nylon resin.
[0038] A method for preparing a high-toughness low-melting-point nylon resin Example 2 (1) 2.022 kg (10.00 mol) of long carbon chain dibasic acid sebacic acid, 2.012 kg (10.04 mol) of long carbon chain diamine dodecanediamine and 1.614 kg of water (40%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1210 salt solution; (2) 403.4 g of ether-bonded amino acid 1-amino-3,6,9,12-tetraoxopentadecane-15-acid, 7.8 g of catalyst sodium hypophosphite and 16.0 g of end-capping agent Shin-Etsu modified silicone oil KF-864 were added to the nylon 1210 salt solution obtained in step (1), and the air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.2 MPa, and then a polycondensation reaction was carried out: first, the temperature was raised to 215°C, and the pressure in the reactor was maintained at 2.2 MPa, and a temperature-raising and pressure-maintaining reaction was carried out for 1.7 h, and then the temperature was continued to be raised to 246°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor at 1.1 MPa, and a second temperature-raising and pressure-maintaining reaction was carried out for 1.5 h later, the pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first, evacuate the system to -0.02 MPa, and then maintain the pressure for 20 min. Then, evacuate the system to -0.04 MPa, and then maintain the pressure for 20 min. Finally, evacuate the system to -0.06 MPa, and then maintain the pressure for 30 min. High-purity nitrogen was then introduced to 0.2 MPa, and the material was discharged to obtain a high-toughness, low-melting-point nylon resin.
[0039] A method for preparing a high-toughness low-melting-point nylon resin Example 3 (1) 2.300 kg (10.00 mol) of long carbon chain dibasic acid dodecanedioic acid, 2.014 kg (10.05 mol) of long carbon chain diamine dodecanediamine and 1.726 kg of water (40%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1212 salt solution; (2) 431.4 g of ether-bonded amino acid 1-amino-3,6,9,12-tetraoxopentadecane-15-acid, 7.9 g of catalyst sodium hypophosphite and 16.2 g of end-capping agent Shin-Etsu modified silicone oil KF-864 were added to the nylon 1212 salt solution obtained in step (1), and the air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.2 MPa, and then a polycondensation reaction was carried out: first, the temperature was raised to 216°C, and the pressure in the reactor was maintained at 2.2 MPa, and a temperature-raising and pressure-maintaining reaction was carried out for 1.8 h, and then the temperature was continued to be raised to 245°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor at 1.1 MPa, and a second temperature-raising and pressure-maintaining reaction was carried out for 1.6 h later, the pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first, evacuate the system to -0.02 MPa, and then maintain the pressure for 20 min. Then, evacuate the system to -0.04 MPa, and then maintain the pressure for 20 min. Finally, evacuate the system to -0.06 MPa, and then maintain the pressure for 30 min. High-purity nitrogen was then introduced to 0.2 MPa, and the material was discharged to obtain a high-toughness, low-melting-point nylon resin.
[0040] A method for preparing a high-toughness low-melting-point nylon resin Example 4 (1) 3.145 kg (10.00 mol) of long-chain dibasic acid octadecane dioic acid, 2.859 kg (10.05 mol) of long-chain diamine octadecane diamine and 3.002 kg of water (50%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1818 salt solution; (2) 600.4 g of ether-bonded amino acid 1-amino-3,6,9,12-tetraoxopentadecane-15-acid, 13.0 g of catalyst sodium hypophosphite and 25.0 g of end-capping agent Shin-Etsu modified silicone oil KF-868 were added to the nylon 1818 salt solution obtained in step (1), and the air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.2 MPa, and then a polycondensation reaction was carried out: first, the temperature was raised to 218°C, and the pressure in the reactor was maintained at 2.5 MPa, and a temperature-raising and pressure-maintaining reaction was carried out for 2.0 h, and then the temperature was continued to be raised to 241°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor at 1.3 MPa, and a second temperature-raising and pressure-maintaining reaction was carried out for 1.8 h later, the pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first, evacuate the system to -0.02 MPa, and then maintain the pressure for 20 min. Then, evacuate the system to -0.04 MPa, and then maintain the pressure for 20 min. Finally, evacuate the system to -0.06 MPa, and then maintain the pressure for 30 min. High-purity nitrogen was then introduced to 0.2 MPa, and the material was discharged to obtain a high-toughness, low-melting-point nylon resin.
[0041] A method for preparing a high-toughness low-melting-point nylon resin Example 5 (1) 2.300 kg (10.00 mol) of long carbon chain dibasic acid dodecanedioic acid, 2.014 kg (10.05 mol) of long carbon chain diamine dodecanediamine and 1.726 kg of water (40%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1212 salt solution; (2) 647.1 g of ether-bonded amino acid 1-amino-3,6,9,12-tetraoxopentadecane-15-oic acid, 8.0 g of catalyst magnesium hypophosphite and 16.5 g of end-capping agent Shin-Etsu modified silicone oil KF-865 were added to the nylon 1212 salt solution obtained in step (1), and the subsequent operation was the same as step (2) of Example 3 of the method of the present invention.
[0042] A method for preparing a high-toughness low-melting-point nylon resin Example 6 (1) 2.300 kg (10.00 mol) of long carbon chain dibasic acid dodecanedioic acid, 2.014 kg (10.05 mol) of long carbon chain diamine dodecanediamine and 1.726 kg of water (40%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1212 salt solution; (2) 862.8 g of ether-bonded amino acid 1-amino-3,6,9,12-tetraoxopentadecane-15-oic acid, 8.3 g of catalyst magnesium hypophosphite and 16.8 g of end-capping agent Shin-Etsu modified silicone oil KF-865 were added to the nylon 1212 salt solution obtained in step (1), and the subsequent operation was the same as step (2) of Example 3 of the method of the present invention.
[0043] A method for preparing a high-toughness low-melting-point nylon resin Example 7 (1) 2.300 kg (10.00 mol) of long carbon chain dibasic acid dodecanedioic acid, 2.014 kg (10.05 mol) of long carbon chain diamine dodecanediamine and 1.726 kg of water (40%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1212 salt solution; (2) 1078.5 g of ether-bonded amino acid 1-amino-3,6,9,12,15,18-hexaoxohexadecan-21-oic acid, 9.0 g of catalyst magnesium hypophosphite and 18.0 g of end-capping agent Shin-Etsu modified silicone oil KF-865 were added to the nylon 1212 salt solution obtained in step (1), and the subsequent operation was the same as step (2) of Example 3 of the method of the present invention.
[0044] Example 8 of a method for preparing a high-toughness low-melting-point nylon resin (1) 2.300 kg (10.00 mol) of long carbon chain dibasic acid dodecanedioic acid, 2.014 kg (10.05 mol) of long carbon chain diamine dodecanediamine and 1.726 kg of water (40%) were added into a reaction kettle and stirred at room temperature to form a salt to obtain a nylon 1212 salt solution; (2) 1294.2 g of ether-bonded amino acid 1-amino-3,6,9,12,15,18,21,24,27-nonaoxatriacontane-30-oic acid, 10.0 g of catalyst magnesium hypophosphite, and 20.0 g of end-capping agent Shin-Etsu modified silicone oil X-22-3701E were added to the nylon 1212 salt solution obtained in step (1), and the subsequent operation was the same as step (2) of Example 3 of the method of the present invention.
[0045] Application Examples 1 to 8 of a High-Toughness Low-Melting-Point Nylon Resin The high-toughness, low-melting-point nylon resin embodiments 1 to 8 are respectively used in the technical fields of automobile oil pipes, water pipes or energy storage equipment hoses.
[0046] Comparative Example 1 The difference between this comparative example 1 and method example 1 is that in step (2), 375.2 g of 1-amino-3,6,9,12-tetraoxopentadecane-15-acid is not added, and 15.0 g of the end-capping agent Shin-Etsu modified silicone oil KF-864 is replaced by 15.0 g of the end-capping agent benzoic acid. The rest is the same as method example 1 of the present invention.
[0047] Comparative Example 2 The difference between this comparative example 1 and method example 1 is that the molar ratio of 2.022 kg (10.00 mol) of long carbon chain dibasic acid sebacic acid and 1.981 kg (11.50 mol) of long carbon chain diamine decanediamine is 1:1.15. The rest is the same as method example 1 of the present invention.
[0048] In order to evaluate the relative viscosity, mechanical properties, heat resistance and water absorption properties of high-toughness, low-melting-point nylon resin Examples 1 to 8 and Comparative Examples 1 and 2 of the present invention, the tests were conducted according to the following test conditions: Relative viscosity test conditions: The samples of the embodiment and the comparative example were placed in a vacuum drying oven at 120° C. for 4 h, and prepared into a concentrated sulfuric acid solution with a concentration of 0.010 g / mL, and tested using an automatic viscometer in accordance with standard GB / T 38138-2019; Tensile strength and elongation at break test conditions: The tensile specimens were placed in a constant temperature and humidity chamber for 24 hours and tested using a testing machine in accordance with standard GB / T 1040.2-2006; Bending strength test conditions: Place the bending specimen in a constant temperature and humidity chamber for 24 hours, and use a testing machine to test according to standard GB / T 9341-2008; Notched impact strength test conditions: place the impact specimen in a constant temperature and humidity chamber for 24 hours, and use a testing machine to test according to standard GB / T 1043.1-2008; Melting point test conditions: Weigh 5-10 mg of the samples of the embodiments and comparative examples, and heat the samples to 340°C for 3 min under the protection of high-purity nitrogen, quench with liquid nitrogen, and then heat the quenched samples to 350°C, cool to room temperature, and then heat to 350°C, with a heating rate of 10°C / min, referring to standard GB / T 19466.3-2004; Water absorption test conditions: The samples of the embodiment and the comparative example were dried in an oven at 100°C, cooled in the oven, and tested according to the standard ASTM D570-98; The results are shown in Table 2.
[0049] Table 2 Performance data comparison table of high-toughness low-melting-point nylon resin embodiments 1 to 8 of the present invention and comparative examples 1 and 2
[0050] As shown in Table 2, the high-toughness low-melting-point nylon resin obtained by the method of Examples 1 to 8 of the present invention has a relative viscosity of up to 2.52, a tensile strength of 47 MPa, an elongation at break of up to 382%, a flexural strength of 68 MPa, and a notched impact strength of up to 32 kJ / m 2, the melting point is as low as 122°C, and the water absorption rate is as low as 0.36%. Compared with Comparative Example 1, the high-toughness, low-melting-point nylon resin obtained in Example 1 of the method of the present invention has significantly improved elongation at break and notched impact strength while maintaining a relatively high mechanical strength, and the melting point decrease ratio is close to 20%; because in Comparative Example 2, the molar ratio of the long carbon chain dibasic acid to the long carbon chain diamine exceeds the range of 1:1.0 to 1.10, resulting in a low relative viscosity of the obtained nylon resin, and the overall performance parameters are significantly reduced. In addition, the method of the present invention has the characteristics of few product by-products, simple production process, and suitability for industrial continuous production. The obtained high-toughness, low-melting-point nylon resin can replace high-performance nylon resin imported from abroad, and is used in technical fields such as automotive oil pipes, water pipes or energy storage equipment hoses.
Claims
1. A high-toughness, low-melting-point nylon resin, characterized in that: The invention is mainly prepared from the following components: a long carbon chain dibasic acid, a long carbon chain diamine, an amino acid containing an ether bond, a catalyst and a capping agent, and water is used as a reaction medium.
2. The high-toughness, low-melting-point nylon resin according to claim 1, characterized in that: The molar ratio of the long carbon chain dibasic acid to the long carbon chain diamine is 1:1.0-1.10; the dosage of the ether bond-containing amino acid, catalyst, end-capping agent and water is 10.0-30.0%, 0.18-0.42%, 0.3-0.8% and 40-50% of the total mass of the long carbon chain dibasic acid and the long carbon chain diamine, respectively.
3. The high-toughness, low-melting-point nylon resin according to claim 1 or 2, characterized in that: The general structural formula of the long carbon chain dibasic acid is HOOC-(CH2) n -COOH, wherein n=an integer of 8 to 16; the general structural formula of the long carbon chain diamine is NH2-(CH2) n -NH2, wherein n=an integer of 10 to 18; the amino acids containing ether bonds include 1-amino-3,6,9,12-tetraoxopentadecane-15-acid, 1-amino-3,6,9,12,15-pentaoxoctadecane-18-acid, 1-amino-3,6,9,12,15,18-hexaoxonicosane-21-acid, 1-amino-3,6,9,12,15,18,21-heptaoxotetracosane-24-acid, 1-amino-3,6,9,12,15,18,21,24-octaoxonicosane-27-acid. Acid, 1-amino-3,6,9,12,15,18,21,24,27-nonaoxatriacontane-30-acid or 1-amino-3,6,9,12,15,18,21,24,27,30-decaoxatriacontane-33-acid; the catalyst includes one or more of sodium hypophosphite, potassium hypophosphite, calcium hypophosphite or magnesium hypophosphite; the end-capping agent includes one or more of monoamino or monocarboxyl organosilicon, Shin-Etsu modified silicone oil KF-864, KF-865, KF-868 or X-22-3701E.
4. A method for preparing the high-toughness, low-melting-point nylon resin as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Adding a long carbon chain dibasic acid, a long carbon chain diamine and water into a reaction kettle, stirring at room temperature to form a salt, and obtaining a nylon salt solution; (2) An amino acid containing an ether bond, a catalyst and a capping agent are added to the nylon salt solution obtained in step (1), the air in the reaction kettle is replaced with an inert gas and filled with the inert gas, a polycondensation reaction is carried out, the inert gas is filled again, and the material is discharged to obtain a high-toughness, low-melting-point nylon resin.
5. The method for preparing the high-toughness low-melting-point nylon resin according to claim 4, characterized in that: In step (2), the specific reaction process of the polycondensation reaction is: firstly carry out a temperature-raising and pressure-maintaining reaction, slowly release the gas and carry out a second temperature-raising and pressure-maintaining reaction, then release the gas to normal pressure, discharge the water in the system, and gradually evacuate the system to carry out a pressure-reducing reaction; the first temperature-raising and pressure-maintaining reaction refers to: heating to 210-220°C, and maintaining the pressure in the autoclave at 2.0-2.5MPa, and reacting for 1.5-2.0h; the slow release and second temperature-raising and pressure-maintaining reaction refers to: continuing to heat to 240-250°C, slowly releasing the gas during the heating process to maintain the pressure in the autoclave at 1.0-1.5MPa, and reacting for 1.0-2.0h; the gradual vacuuming Carrying out a reduced pressure reaction means: first evacuating to -0.01 to -0.03 MPa, then maintaining the pressure for 15 to 25 minutes, then evacuating to -0.03 to -0.05 MPa, then maintaining the pressure for 15 to 25 minutes, and finally evacuating to -0.05 to -0.07 MPa, then maintaining the pressure for 12 to 30 minutes; before the polycondensation reaction, replacing the air in the reaction kettle with an inert gas 3 to 4 times and filling it with an inert gas to 0.1 to 0.2 MPa; after the polycondensation reaction, filling it with an inert gas to 0.2 to 0.3 MPa; the inert gas includes one or more of carbon dioxide, nitrogen, argon or helium.
6. An application of the high-toughness, low-melting-point nylon resin as claimed in any one of claims 1 to 3, characterized in that: The high-toughness, low-melting-point nylon resin according to any one of claims 1 to 3 is used in the technical field of automobile oil pipes, water pipes or energy storage equipment hoses.
Citation Information
Patent Citations
Method for synthesizing dimer acid type polyamide hot melt adhesive
CN102492135A
Amino-functionalized-polyolefin-elastomer-toughened nylon composite material and production method thereof
CN109722020A
Preparing method of ternary polymerization low-melting-point nylon
CN109970969A
Method for preparing semi-aromatic polyamide with improved impact strength, semi-aromatic polyamide and molding composition
CN114133560A
Copolyamides and polymer membranes comprising at least one diamine, dicarboxylic acid and 1, 5-diamino-3-oxapentane
CN117999307A
Cited By
Ternary copolymerized nylon resin as well as preparation method and application thereof
CN120173236A